(untitled) (FAVE Sección Ciencias Veterinarias, 2018)
In horses parasitized by small strongyles, a shortened strongyle egg reappearance period (ERP) after treatment with anthelmintics is considered an early indicator of the presence of resistance or loss of efficacy to these drugs. In the present work, clinical efficacy and ERP were evaluated after treatments with ivermectin in adult horses (broodmares) and juveniles (its fillies) naturally parasitized by small strongyles in an farm of Tucumán province. The clinical efficacy determined in the second week after treatment, and using a test of reduction in the egg count, ranged between 99.8 and 100% in mares and fillies respectively. The ERP (considered as the post- treatment period in which 10% of the pre-treatment epg was reached or a reduction of it < 90%) was six and seven weeks for the fillies and mother mares respectively (p= 0.001). In the sixth week after treatment, the fillies showed 11.74 times more risk (95% CI = 2.58-53.38) of reappearance of eggs than the brood mares. These differences caused by the age of the animals should be considered when conducting studies to establish the status of susceptibility or resistance to anthelmintics based on the ERP to avoid incorrect assumptions.